Greening TVET for a Sustainable Future - Bagale, Shiba (Journal of Training and Development, 2026)
There are several environmental challenges faced by the world, and providing green jobs for a green economy through Technical and Vocational Education and Training (TVET) is seen as a way forward. This review article on Greening TVET integrates skills for sustainable practices, green skills, green curriculum, and programs. The policies, curriculum integration, awareness, and industry institution linkage to share sustainable practices are an urgent need which needs to be planned and implemented. Some of the practices are seen in the context of greening TVET in Nepal. But the continuation of incorporating the gaps between what is and what needs to be is needed. The strategies focused on in this review article are: incorporating Greening TVET into all policies and governance, including the curriculum; increasing teachers’ capacity development programs; fostering industry partnerships; practicing green practices by schools; and conducting research on greening TVET. So, reforms to institutions in terms of greening, policy support, partnerships, and linkages with industry to develop green skills and prepare graduates for the labour market are essential to fully realize the potential of greening TVET as an enabler of sustainable development and a sustainable future in Nepal.